Effect of FMD vaccination on various semen quality parameters in Frieswal crossbred bulls - SIROHI, A S; CHAND, N; TYAGI, S; SRIVASTAVA, N; SHARMA, A; HEMLATA, HEMLATA (The Indian Journal of Animal Sciences, 2016)
The primary objective of the present study was to assess the semen quality parameters in Frieswal crossbred bulls (95) after vaccination against foot and mouth disease (FMD). The fresh ejaculates (3,537) were subjected to evaluation for volume, concentration, initial motility and post-thaw motility as per standard procedures. The observations were recorded for 1 month of pre-vaccination and 5 months post-vaccination. A steadily decrease in the volume of semen was observed during post-vaccination period. No significant change was observed in concentration and live percentage of spermatozoa during post-vaccination period. However, percentage of total abnormal spermatozoa increased from 14.50% in pre-vaccination period to 25.32% in first month of post-vaccination period. Initial motility of spermatozoa decreased significantly following the FMD vaccination in bulls up to third month but started increasing from fourth month of post-vaccination. No difference was observed in post-thaw motility of ejaculates selected for freezing during first 3 months of post-vaccination. It was evident in the present study that semen quality parameters of Frieswal crossbred bulls improved after three months of FMD vaccination.